2018
DOI: 10.12681/bgsg.16543
|View full text |Cite
|
Sign up to set email alerts
|

Petrified Wood Occurrences in Western Thrace and Limnos Island: Mineralogy, Geochemistry and Depositional Environment

Abstract: The present study describes the geology and mineralogy of the main petrified wood occurrences in Evros-Rhodopi and Limnos and integrates them in a volcanichydro thermal framework taking into consideration the nature of hydrothermal solu-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 4 publications
2
17
0
Order By: Relevance
“…Smectite, zeolites and calcite are accessory minerals both within the veins and in the wall rocks ( Figure 4b). Similar to Kassiteres-Sapes area, in the broad Kornofolia area, the amethyst-chalcedony veins crosscut fossiliferous limestone reefs and silicified wood hosted in volcano-sedimentary layers, thus suggesting a very shallow submarine to transitional environment [41], and accordingly a very shallow depth of amethyst formation, probably close to the seafloor. Unaltered to zeolite-altered lavas of dacitic composition are the host rocks of chalcedonyamethyst bearing NNW-trending veins at Kirki area, in a locality resembling that of Kornofolia (Figures 1b and 3f).…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Smectite, zeolites and calcite are accessory minerals both within the veins and in the wall rocks ( Figure 4b). Similar to Kassiteres-Sapes area, in the broad Kornofolia area, the amethyst-chalcedony veins crosscut fossiliferous limestone reefs and silicified wood hosted in volcano-sedimentary layers, thus suggesting a very shallow submarine to transitional environment [41], and accordingly a very shallow depth of amethyst formation, probably close to the seafloor. Unaltered to zeolite-altered lavas of dacitic composition are the host rocks of chalcedonyamethyst bearing NNW-trending veins at Kirki area, in a locality resembling that of Kornofolia (Figures 1b and 3f).…”
Section: Introductionmentioning
confidence: 65%
“…Prismatic amethyst crystals are rare. The presence of silicified wood within the tuffs hosting amethyst veins at Kassiteres-Sapes area, and the observation that the amethyst veins crosscut the fossilized wood [41], indicate probably a very shallow environment for amethyst deposition.…”
Section: Introductionmentioning
confidence: 96%
“…Synthesizing previous views on the geological evolution of Evros, Voudouris et al (2007) showed that the main phase of Cenozoic magmatism took place during the Oligocene until the earliest Miocene (Innocenti et al 1984, Del Moro et al 1988 and is represented by submarine/terrestrial volcanic and subvolcanic rocks. Christofides et al (2004) give radiometric ages of 30-28 Ma for the area north of Tycheron, which suggests late Rupelian/early Chattian age.…”
Section: Geological Setting Of the Greek Areas Of Palaeobotanical Intmentioning
confidence: 70%
“…According to Kopp (1965), Petrescu et al (1980) and Velitzelos et al (2002), the fossil plants are related mainly to the Rupelian-Chattian lignite-bearing volcano-sedimentary levels of the Provatonas series (around Fylakto village), which discordantly cover the volcanics. Coral reefs and abundant mollusks within the silt layers, indicating a shallow marine environment, have been observed (Kopp 1965, Voudouris et al 2007. Around Lefkimi village, rocks of rhyolitic and andesitic composition appear in a submarine environment (as hyaloclastites) and are overlain by coral-bearing reefs and then by fine-grained volcano-sedimentary layers including silicified wood.…”
Section: Geological Setting Of the Greek Areas Of Palaeobotanical Intmentioning
confidence: 99%
See 1 more Smart Citation